Health Literacy and Personality Traits in Two Types of Family Structure—A Cross-Sectional Study in China - Mai, Jianrong; Yibo, Wu; Ling, Zhou; Lina, Lin; Xinying, Sun (Frontiers in Psychology, 2022)
Objective: The level of health literacy is one of the important factors affecting health outcomes. Family is an important place to shape personality traits, and people with different personalities will adopt different lifestyles, which will lead to variations in health outcomes. Therefore, this article aims to explore the relationship between health literacy and personality and its influencing factors in different family structures. Method: This was a cross-sectional study with 1406 individuals. A questionnaire was utilized to measure health literacy, personality and demographic variables, including family structure. Canonical correlation analysis (CCA) and hierarchical multiple regression analysis were used to examine the relation between health literacy and personality traits between two types of family structure. Results: CCA showed that the canonical correlation coefficients were 0.309 (p<0.001) and 0.347 (p<0.001), in two-parent family and single-parent family, respectively. The openness of personality traits exhibited the highest correlation with health literacy. Compared with the remaining personality traits, openness yielded the strongest effect (β=0.485 and β=0.830) in two types of family structure, respectively. Education and monthly income were significantly associated with health literacy. Conclusions: Our results support the relation between health literacy and personality traits in two types of family structure.